Regularity for Variational Evolution Integrodifferential Inequalities - Yong Han Kang; Jin-Mun Jeong (Abstract and Applied Analysis)
We deal with the regularity for solutions of nonlinear functional integrodifferential equations governed by the variational inequality in a Hilbert space. Moreover, by using the simplest definition of interpolation spaces and the known regularity result, we also prove that the solution mapping from the set of initial and forcing data to the state space of solutions is continuous, which very often arises in application. Finally, an example is also given to illustrate our main result.